Investigation of cds photoconductivity spectra dependence from the direction of spectrum scanning - A. S. Batirev; R. A. Bisengaliev; N. K. Shividov; M. O. Tahirov (Наука. Инновации. Технологии)
The low-temperature (77 K) photoconductivity spectra of CdS crystals has been investigated in the absorption edge region vs the scanning direction of the excitation light wavelength. It is shown that the observed hysteresis of semiconductor photoconductivity spectral dependence can be due to the optical recharge of r-center - the deep compensated acceptor as-sociated with the shallow donor.